Implementation of new standard operating procedures for geriatric trauma patients with multiple injuries: a single level I trauma centre study - Lorenz Peterer; Christian Ossendorf; Kai Oliver Jensen; Georg Osterhoff; Ladislav Mica; Burkhardt Seifert; Clément M. L. Werner; Hans-Peter Simmen; Hans-Christoph Pape; Kai Sprengel (BMC Geriatrics, 2019)
Abstract Background The demographic changes towards ageing of the populations in developed countries impose a challenge to trauma centres, as geriatric trauma patients require specific diagnostic and therapeutic procedures. This study investigated whether the integration of new standard operating procedures (SOPs) for the resuscitation room (ER) has an impact on the clinical course in geriatric patients. The new SOPs were designed for severely injured adult trauma patients, based on the Advanced Trauma Life Support (ATLS) and imply early whole-body computed tomography (CT), damage control surgery, and the use of goal-directed coagulation management. Methods Single-centre cohort study. We included all patients ≥65 years of age with an Injury Severity Score (ISS) ≥ 9 who were admitted to our hospital primarily via ER. A historic cohort was compared to a cohort after the implementation of the new SOPs. Results We enrolled 311 patients who met the inclusion criteria between 2000 and 2006 (group PreSOP) and 2010–2012 (group SOP). There was a significant reduction in the mortality rate after the implementation of the new SOPs (P = .001). This benefit was seen only for severely injured patients (ISS ≥ 16), but not for moderately injured patients (ISS 9–15). There were no differences with regard to infection rates or rate of palliative care. Conclusions We found an association between implementation of new ER SOPs, and a lower mortality rate in severely injured geriatric trauma patients, whereas moderately injured patients did not obtain the same benefit. Trial registration Clinicaltrials.gov NCT03319381, retrospectively registered 24 October 2017.